Less Physical Activity and Inappropriate Food Consumption were Risk Factors for Diabetes Mellitus and Hypertension among Risk Group in Khokkhian Subdistrict, Mueang District, Narathiwat Province - พรหมสงค์ อรฤทัย; หวังแอ อัยนาอ์; ทองวิเศษ กษิตินาถ; จตุรพิธพรรัตน์ ชนาธิป; สุวรรณนิตย์ วุฒิพงศ์ (Princess of Naradhiwas University Journal, 2019)
The objectives of this study were to investigate knowledge, risk factor awareness, and risk behaviors with the factors associated risk behaviors of the risk groups in diabetes mellitus (DM) and hypertension. A total of 244 participants at risk aged 45 years and over were recruited from Khokkhian subdistrict, Mueang district, Narathiwat Province. Questionnaires were used as the instrument for data collection with the assessment of content validity (IOC =0.76). Descriptive statistics and Chi-square tests were performed for data analysis. The result showed that participants had 53.9% of body mass index (BMI) higher than standard level. Regarding to diabetes and hypertension, the high level of knowledge was 77.5% and 75.4%, whereas the moderate level of awareness of risk factor was 53.3% and 42.2%, respectively. However, overall risk behaviors of diabetes and hypertension were moderate level ( =0.77). Moreover, positive/protective factors-taking behaviors were poor practice; stress, alcohol drinking and smoking, including taking drug and hormone. On the other hand, negative/risk factors-taking behaviors were food consumption and physical activity. The physical activity was significant correlated with education (p=.005) and income (p<.001). Participants with primary school and average income (less than 6,000 baht per month) presented risk of diabetes and hypertension due to less physical activity and more consumption of fried food and dessert. That was consistent with a higher percentage of BMI than the range of standard